1999
DOI: 10.1103/physreve.59.7042
|View full text |Cite
|
Sign up to set email alerts
|

Self-focusing, channel formation, and high-energy ion generation in interaction of an intense short laser pulse with a He jet

Abstract: Sarkisov, G.S.; Bychenkov, B. Yu.; Novikov, V.N.; Tikhonchuk, V.T.; Maksimchuk, Anatoly; Chen, Shouyuan; Wagner, R.; Mourou, G.; and Umstadter, Donald, "Self-focusing, channel formation, and high-energy ion generation in interaction of an intense short laser pulse with a He jet" (1999 Using interferometry, we investigate the dynamics of interaction of a relativistically intense 4-TW, 400-fs laser pulse with a He gas jet. We observe a stable plasma channel 1 mm long and less than 30 m in diameter, with a radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
101
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(112 citation statements)
references
References 37 publications
9
101
2
Order By: Relevance
“…The development of shortpulse high-intensity lasers 2 made it possible to accelerate protons and heavier ions to multi-MeV energies in the interaction of these lasers with solid targets, [3][4][5][6] gas jets, 7 and clusters. 8 It was shown that these accelerated protons can induce nuclear transformations.…”
mentioning
confidence: 99%
“…The development of shortpulse high-intensity lasers 2 made it possible to accelerate protons and heavier ions to multi-MeV energies in the interaction of these lasers with solid targets, [3][4][5][6] gas jets, 7 and clusters. 8 It was shown that these accelerated protons can induce nuclear transformations.…”
mentioning
confidence: 99%
“…The first publication about the shearing air wedge interferometer was done in 1996 2 and it was applied successfully to investigating the Coulomb explosion phenomena [3][4][5] due to interaction of a 400 fs 10 TW laser with a gaseous target, and to other laser plasma and Z-pinch investigations as well. Because the authors of Ref.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Energetic ions from underdense plasmas were accelerated by an electrostatic sheath, which was created by charge-displacement. Unlike earlier long-laser-pulse experiments, the displacement was due not to thermal expansion but to ponderomotive blow-out [13,14]. When a helium-gas was used as the target, alpha particles were accelerated to several MeV in the direction orthogonal to the direction of laser propagation and along the direction of the maximum intensity gradient.…”
Section: Nozzlementioning
confidence: 92%